IMPLEMENTATION OF ERGONOMIC PRINCIPLE ON RATTAN (Calamus spp.) HANDICRAFT AT SMALL MEDIUM INDUSTRY UD. ELSINDO IN RUMBAI PEKANBARU RIAU PROVINCE - Muhammad Iqbal; Evi Sribudiani; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2018)
Ergonomics is study of human to create work system healthier, safer and more comfortable. The concept of ergonomics and occupational safety and health equipment have to apply in industry, from small medium scale untill upper medium. UD. Elsindo is one of micro small enterprise that still developing and need the implementation ergonomic principles especially occupational safety and health equipment in processing rattan in order to achieve work productivity. Visually rattan handicraft industry UD. Elsindo have not applied ergonomic principles especially occupational safety and health equipment in processing rattan. When processing the rattan, the employees do the direct contact with the tools and substance that can cause accident if they are not implement the ergonomic principles. The data has been collected by observation, interview and documentation. UD. Elsindo is individual businesses that owned by Sugianto in 1994. The employees are 11 with 4 journeyman and 7 jobholder. The products is dominate by house ware which is guest chairs, dinning chairs, rocking chairs, food covers and others. The other products that produce by UD. Elsindo are toys, baby swings, takraw balls, hulahoop and others. UD. Elsindo have not applied the ergonomic principles that compatible with ILO and constitution of occupational safety and health equipment in every rattan processing. The factors are because the business owner is les assertive in applying the rules, the employees do not have knowledge about ergonomic principles and also they are comfortable without applying personal protective equipment in processing the rattan.